The role of the green human resources management practices in a achieving requirements of environmental citizenship- Field research at the General Company for Vegetable Oils. - تناي غني دحام (Journal of Economics and Administrative Sciences, 2016)
The research aims to determine the role of the practices of green human resources management in achieving requirements of environmental citizenship in the workplace, the General Company for Vegetable Oils was chosen for the application of field-side of research which represent one of the important industrial companies in Iraq, which suffers from poor Green human resources management applications, which reflected negatively on the development Environmental citizenship among Employees. The questionnaire use as a tool to collect data and information as well as field presence of the researcher, The research sample included (30) managers of departments and Division ,and through using statistical program (SPSS) the data has been analysis and Perhaps the most prominent results are the weakness of the adoption of green human resource management practices by the company and the weakness of the prevalence of a culture of environmental citizenship among employees. The most important recommendations that came out of research are an emphasis on attention to green human resources management practices across activities of the , employment , training , compensation and incentive systems and performance evaluation, and so as to support environmental citizenship among employees.